A comprehensive review of advances in ultrasonic vibration machining on SiCp/Al composites - Zhaojie Yuan; Daohui Xiang; Peicheng Peng; Zhiqiang Zhang; Binghao Li; Mingyang Ma; Zhipeng Zhang; Guofu Gao; Bo Zhao (Journal of Materials Research and Technology, 2023)
On account of the remarkable mechanical properties, SiCp/Al composites are extensively utilized in the aerospace industry, exhibiting a vast scope of applications. However, the extremely hard particle reinforcement leads to poor machining quality, high cutting resistance, and severe tool wear in traditional machining, resulting in poor machinability and difficulty in meeting the requirements for high surface quality and low damage. The processability of SiCp/Al composites has been enhanced through the implementation of ultrasonic vibration machining technology. An overview of the influence of ultrasonic vibration machining on the machining properties of SiCp/Al composites is presented in this study, covering different forms of ultrasonic vibration machining, vibration devices, and theoretical analysis, analyzing the intermittent separation behavior of tool and workpiece using cutting forces, surface topography, and tool wear as assessment criteria. The development direction of the multi-energy field ultrasonic vibration composite machining technology for SiCp/Al composites is also outlooked. The challenges of ultrasonic vibration technology in the fabrication of SiCp/Al composites include the theory of vibration propagation in non-uniform media, the theory of multi-energy field coupling, the design theory of vibration devices, and the microscopic removal mechanism of materials under ultrasonic energy impact. Therefore, theoretical breakthroughs and device improvements play an important role in future research on ultrasonic vibration machining of SiCp/Al composites.